Effect of promoters on the morphology of Ni-based catalyst - Yahya, E.A. (American Institute of Physics Inc., 2015)
In this paper, effect of promoters on the morphology of Ni-based catalyst supported on Al 2 O 3 was studied. Ni/Al 2 O 3 catalysts doped with Co, Cu, Mn and Nb were synthesized via impregnation method. The catalysts were characterized by FESEM and TEM. Results of FESEM and TEM analyses show that the morphological properties of the catalysts were affected by the type of promoter used. Hexagonal shape particles in 9Ni-1Mn/Al 2 O 3 and 9Ni-1Nb/Al 2 O 3 were observed. Unpromoted catalysts has spherical shape particles and has the smallest average particle size of 5.42 nm compared to other promoted catalysts. Â© 2015 AIP Publishing LLC.